Relationship between Transformational and Transactional Leadership Styles and commitment to Change : The case of Higher Education in Malaysia - May-Chiun , Lo; Ramayah, T.; Ernest Cyril , de Run (-, 2014)
This paper hypothesized that the leadership styles of supervisors was anchored on four types of commitment to change of the subordinates. Transactional and transformational were conceptualized as 4-and 3-dimensional constructs, respectively. The research uses a sample of 19 public universities located in Malaysia. Findings suggested that individualized consideration, idealized influence, and inspirational motivation were found to have positive relationship with personal goals arousal and context belief dimensions of commitment to change. Contingent reward and passive management by exception were found to be positively related to capacity belief and personal goals arousal dimensions of commitment to change. Implications of the findings, potential limitations of the study, and directions for future research were further discussed.